Meter and modernity in English verse, 1350-1650 - Weiskott, Eric (Philadelphia : University of Pennsylvania Press, 2021)
Eric Weiskott examines the uses and misuses of three metrical forms as markers of literary periodization: alliterative meter, tetrameter, and pentameter. Rejecting the traditional division between medieval and modern, Weiskott's analysis of metrical history renegotiates the trajectories of English literary history between 1350 and 1650.
English political prophecy: coordinates of form and history -- The age of prophecy -- The Ireland prophecy and the future of alliterative verse -- Tetrameter: the future of alliterative verse -- Where have all the pentameter prophecies gone? -- lliterative meter and blank verse, 1540-1667 -- The rhymelessness of Piers Plowman -- Langland's meter and blank verse, 1700-2000 -- Chaucer and the problem of modernity -- Chaucer's English metrical phonology: tetrameter to pentameter -- The age of pentameter
Includes bibliographical references and indexes
Print version record
JSTOR
Keywords: English language -- Versification; English poetry -- Middle English, 1100-1500 -- History and criticism; English poetry -- Early modern, 1500-1700 -- History and criticism; Poetics -- History; English literature -- Periodization; Anglais (Langue) -- Versification; Poésie anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Poétique -- Histoire; LITERARY CRITICISM -- Medieval; English language -- Versification; English literature -- Periodization; English poetry -- Early modern; English poetry -- Middle English; Poetics; 1100-1700; Cultural Studies; Literature; Criticism, interpretation, etc; History; Literary criticism; Literary criticism; Critiques littéraires.